Implementasi Kebijakan Pembayaran Parkir Menggunakan Transaksi Elektronik di Jalan Serayu Kota Surabaya - Ira Febriana; Tjitjik Rahaju; Indah Prabawati; M. Noer Falaq Al Amin (Perspektif Administrasi Publik dan hukum, 2026)
The management of on-street parking in Surabaya continues to face problems, including illegal parking, unauthorized parking attendants, and noncompliance with established parking fees. In response, the Surabaya City Government introduced an electronic parking payment policy to improve service quality, order, safety, and local revenue. However, its implementation remains constrained by malfunctioning parking meters, the public’s preference for cash payments, and unmet revenue targets. This study aims to describe the implementation of the electronic parking payment policy on Serayu Street, Surabaya. A descriptive qualitative approach was employed, with data collected through interviews, observations, and document analysis. The analysis refers to George C. Edwards III’s policy implementation model, covering communication, resources, disposition, and bureaucratic structure. The findings indicate that internal communication is effective, although public outreach remains limited. Operational staff are adequate, but the number of supervisors and available budget are insufficient. Policy implementers generally demonstrate a supportive attitude, although the cashless payment system has not been applied consistently. The bureaucratic structure is supported by clear standard operating procedures and supervision mechanisms. Therefore, greater public awareness, stronger supervision, and additional training for parking attendants are required.